PENGEMBANGAN ENSIKLOPEDIA TARI TRADISIONAL MATERI SENI BUDAYA DAN PRAKARYA (SBDP) PADA KELAS V SEKOLAH DASAR - Dwi Rizki Safitri; Tri Ariani; Armi Yuneti (LP4MK STKIP PGRI Lubuklinggau, 2023)
This study aims to develop an Encyclopedia of Traditional Dance Materials for Cultural Arts and Crafts in grade V Elementary School according to the 2013 curriculum to produce valid, practical and effective media for use in learning. The research model used is research and development (RnD) with the four-D development model. The research sample consisted of 30 students and the instruments used were pretest and posttest. The techniques used in this study were observation, interviews and questionnaires. Based on the results of the assessment analysis by the three experts, namely: linguists 0.92, media experts 0.87 and material experts 0.87, it shows that the Encyclopedia of Traditional Dance for Cultural Arts Materials meets the very valid criteria. While the results of the research on teacher practicality sheets obtained an average of 87.5% and students consisting of 6 people obtained an average of 95% that the Traditional Dance Encyclopedia met the very practical criteria. And the results of the research on the effectiveness of class V students obtained N-gain (g) results of 0.85, the Encyclopedia of Traditional Dance meets the high classification, so it can be concluded that the Encyclopedia of Traditional Dance for Cultural Arts and Crafts Materials meets the valid, practical and effective criteria and can be used in learning. Keywords: Encyclopedia, SBdP, Elementary School